Cathodic Protection of Marine Prestressed Concrete Bridges – Review of Case Studies - Sharma Suraksha; Hornbostel Karla; Geiker Mette (Nordic Concrete Research)
Reinforcement corrosion is the main deterioration mechanism in marine exposed reinforced concrete structures. Recent investigations show that not only the ordinary reinforcement, but also prestressed tendons might be affected. The present paper discusses considerations in connection with the potential application of cathodic protection (CP) systems on marine prestressed concrete bridges. It mainly addresses the potential problems associated with CP application by reviewing several case studies.